Immunobiological Activity of Synthetically Prepared Immunodominant Galactomannosides Structurally Mimicking Aspergillus Galactomannan - Paulovičová, Ema; Paulovičová, Lucia; Hrubiško, Martin; Krylov, Vadim B.; Argunov, Dmitry A.; Nifantiev, Nikolay E. (Frontiers in Immunology, 2017)
The study is oriented at the in vitro evaluation of the immunobiological activity and efficacy of synthetically prepared isomeric pentasaccharides representing fragments of Aspergillus fumigatus cell-wall galactomannan and containing β-(1→5)-linked tetragalactofuranoside chain attached to O-6 (GM-1) or O-3 (GM-2) of a spacer-armed mannopyranoside residue. These compounds were studied as biotinylated conjugates which both demonstrated immunomodulatory activities on the RAW 264.7 cell line murine macrophages as in vitro innate immunity cell-model. Immunobiological studies revealed time- and concentration-dependent efficient immunomodulation. The proliferation of RAW 264.7 macrophages was induced at higher concentration (100 μg/mL) of studied glycoconjugates and longer exposure (48 h), with more pronounced efficacy for GM-1. The increase of proliferation followed the previous increase of IL-2 production. The cytokine profile of the macrophages treated with the glycoconjugates was predominantly pro-inflammatory Th1 type with significant increase of TNFα, IL-6 and IL-12 release for both glycoconjugates. The RAW 264.7 macrophages production of free radicals was not significantly affected by glycoconjugates stimulation. The phagocytic activity of RAW 264.7 cells was reduced following GM-1 treatment and was significantly increased after 24h stimulation with GM-2, contrary to 48 h stimulation. Moreover, the synthetically prepared galactomannoside derivatives have been evaluated as efficient serodiagnostic antigens recognized by specific Ig-isotypes, and significant presence of specific IgM antibodies in serum of patients suffering from vulvovaginitis was observed.